Fresno's Human Services Coalition Luncheon Honoring Karen Humphrey - Watkins, Howard::::::::: (1985)
Jackie Ryle and Karen Humphrey embracing; seated: Supervisor Judy Andreen and Fresno County Economic Opportunities Commission Director Joe Williams